2020
DOI: 10.3389/fcimb.2020.00344
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies Interactions Between Streptococcus Mutans and Streptococcus Agalactiae in vitro

Abstract: Streptococcus mutans is an oral species closely associated with dental caries. As an early oral colonizer, S. mutans utilizes interspecies coaggregation to promote the colonization of subsequent species and affect polymicrobial pathogenesis. Previous studies have confirmed several adhering partner species of S. mutans , including Candida albicans and Fusobacterium nucleatum . In this study, we discovered new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 73 publications
(96 reference statements)
1
5
0
Order By: Relevance
“…Based on the HOMINGS assay, S. mutans was detected in the infant saliva in very low numbers, along with S. sanguinis and other taxa of oral Streptococcus species. The results confirmed that S. mutans may be one of the early colonizers in infant saliva and a critical facilitator for establishing a Streptococcus-associated oral polymicrobial community (42). Furthermore, the core genera in the newborn saliva included not only Streptococcus but also Rothia, Gemella, Veillonella, Staphylococcus, Prevotella, and Granulicatella.…”
Section: Discussionsupporting
confidence: 62%
“…Based on the HOMINGS assay, S. mutans was detected in the infant saliva in very low numbers, along with S. sanguinis and other taxa of oral Streptococcus species. The results confirmed that S. mutans may be one of the early colonizers in infant saliva and a critical facilitator for establishing a Streptococcus-associated oral polymicrobial community (42). Furthermore, the core genera in the newborn saliva included not only Streptococcus but also Rothia, Gemella, Veillonella, Staphylococcus, Prevotella, and Granulicatella.…”
Section: Discussionsupporting
confidence: 62%
“…For instance, this polysaccharide only binds to SspB expressed by Lactococcus lactis, but does not bind to other L. lactis AgI/II family proteins (Back et al, 2015). A recent study showed that the novel intrageneric coadhesion between S. agalactiae and S. mutans is promoted by glucoside transferase B (GtfB) and GtfC (Liu et al, 2020). Another investigation showed that none of the six Lactobacillus strains tested, including clinical isolates from children with caries, could form biofilms in vitro.…”
Section: Bacterial Interactions During Biofilm Formationmentioning
confidence: 99%
“…It is also possible that the different response of the two microorganisms studied here may be due to a greater initial cell surface area (at matching CFU/mL) for C. albicans compared to S. mutans. While C. albicans are larger cells at 5–6 ”m [ 57 ], S. mutans have an average cell size of 0.5–0.75 ”m [ 58 ]. The lack of dependence of the MIC and MBC on the light application mode for S. mutans is likely due in part to the reduced molar absorptivity of curcumin in BHI.…”
Section: Discussionmentioning
confidence: 99%